Qasimjon ABIDOV (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the approach and evidentiary arguments of Hanafi hadith scholars regarding the hadiths transmitted on the issue of “raf’ul-yadayn” (raising the hands) in prayer. By examining the various hadiths concerning this practice, the evidentiary bases advanced by scholars of the Hanafi school on this issue, as well as the extent of their probative strength, have been analyzed. In addition, a comparative analysis has been conducted with the approaches of other juristic schools to this issue, thereby elucidating the distinctive characteristics of the Hanafi school. The responses of Hanafi jurists to the evidences advanced by scholars of other schools have also been examined in brief.
Keywords: raf’ul-yadayn; hadith; school of law (madhhab); mujtahid; Companion (ṣahabi); juristic disagreement (ikhtilaf); legal reasoning/evidentiary argumentation (istidlal)